Endodontic Treatment of Bilateral Mandibular First Premolars with Three Root Canals: A Report of Two Cases - Dalaei Moghadam, Maryam; Farahi, Forough (Iranian Endodontic Journal, 2021)
Correct diagnosis of root canal anatomy is very important to ensure successful root canal treatment. Mandibular first premolars with three separate root canals are very rare. Consequently, they often require specific shaping and obturating techniques. This report describes the diagnosis and non-surgical treatment(s) of bilateral mandibular first premolars with three separate root canals.